High-density powder metallurgy valve seat ring and preparation method thereof

Through the preparation method of powder metallurgy valve race without copper elements, strengthened base powder and high alloy powder of Fe, P and other elements are used to form eutectic semi-liquid phase structure, solving the problem of decreasing density and wear resistance of copper seepage race under high temperature environment, achieving high density, strength and wear resistance effects, and simplifying the process flow.

CN119553189APending Publication Date: 2025-03-04ANQING TP POWDER METALLURGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411705854.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing copper seepage valve races are prone to melting and loss of Cu particles in high temperature and high pressure environments, resulting in a decrease in density, strength and wear resistance, and the process is cumbersome and cost is high.

Method used

The preparation method of powder metallurgical valve race without copper elements is adopted, and reinforced base powder containing elements such as Fe, P and high alloy powder are used to form 22-30% eutectic semi-liquid phase structure through high-temperature sintering and deep-cold treatment to enhance the bonding strength of metal bonds.

Benefits of technology

High density, strength and wear resistance in high temperature and high pressure environments are achieved, which avoids the problem of Cu melting loss, while simplifying the process flow and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553189A_ABST
    Figure CN119553189A_ABST
Patent Text Reader

Abstract

The invention relates to a high-density powder metallurgy valve seat ring and a preparation method thereof. The powder metallurgy valve seat ring is formed by pressing and sintering powder raw materials after the powder raw materials are evenly mixed. The powder raw material comprises the following elements in percentage by mass: 1.0 to 2.0 percent of C, 0.3 to 1.2 percent of S, 6.0 to 14.0 percent of Mo, 20.0 to 35.0 percent of Co, 5.0 to 11.0 percent of W, 2.0 to 8.0 percent of V, 3.0 to 9.0 percent of Cr, 0.3 to 1.2 percent of Mn, 0.2 to 1.0 percent of Ni, 0.1 to 1.0 percent of P and the balance of Fe. The powder raw material is formed by mixing reinforced base powder, alloy powder and basic additive components; the reinforced base powder contains W, Cr, V, P and Fe, and the P element exists in the form of FeP3. The Fe-based alloy powder in the valve seat ring can dissolve part of P atoms to generate 22-30% of eutectic semi-liquid phase structures, so that solid-phase alloy particles get close to one another, and the particles are bonded to one another to form metal bonds with high bonding strength. The copper-free copper alloy does not contain copper, and Cu melting loss does not occur in a high-temperature and high-detonation-pressure environment. And the high-temperature, high-pressure, lubrication-free and other harsh working environments of high-combustion-efficiency gas machines and high-detonation-pressure engines can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of valve seat rings, and in particular to a high-density powder metallurgy valve seat ring and a preparation method thereof. Background Art

[0002] Energy resources are becoming increasingly scarce, and the implementation of the national "carbon peak" and "carbon neutrality" strategies has led to the upgrading and development of traditional internal combustion engines towards "high thermal efficiency, low energy consumption, low emissions, and alternative fuels". Since the implementation of the National VI emission standards in 2019, my country will fully implement the 6b stage of domestic emission standards nationwide from July 1, 2023, and prohibit the production and sale of vehicles that do not meet the 6b stage of the National VI emission standards. In 2022, the EU announced the Euro VII emission standard proposal, and plans to strictly control vehicle exhaust emissions such as CO, NOx and fine emissions from July 2025. In the next few years, my country will also introduce the more stringent National VII standard, which requires optimization of the drive system calibration and upgrading of the exhaust treatment system. Specific improvements include: adding EGR (exhaust gas recirculation system), improving fuel injection methods, improving engine combustion chamber structure, improving fuel system sealing, etc. Traditional internal combustion engines will develop towards the trend of "higher temperature, greater explosion pressure, and cleaner emissions". These have put forward higher requirements on the high temperature resistance, wear resistance, and durability of related automotive parts. Faced with the upcoming National VII emission standards, our automotive parts companies need to continue to innovate in technology from aspects such as material performance upgrades, structural design optimization or surface treatment.

[0003] The valve seat and valve are important components of the engine valve train. The main function of the valve seat is to closely match the working surface (sealing surface) with the valve cone surface to ensure the sealing of each combustion chamber of the engine. At the same time, the valve seat and valve constitute the channel for gas exchange between the engine combustion chamber and the external environment. In the field of powder metallurgy automotive parts, in order to improve the thermal conductivity, wear resistance and overall density of the valve seat in diesel engines and gas engines, the general process is to copperize the seat. The copper infiltration process of the seat is to first press the density of the seat blank to 6.3~6.7g / cm3 (the maximum density of the high alloy seat can only be ≤6.9g / cm3), and then perform copper infiltration and cold and hot treatment processes, and the density can be increased to 7.5~8.2g / cm3. After the seat ring is infiltrated with copper, although its density, strength and thermal conductivity have been improved to a certain extent, there are still some shortcomings: ① The melting point of pure Cu is 1083℃, but the melting point of Cu alloy (containing a certain proportion of slag-forming agent mixture components such as Mn, Si, Fe, etc.) as the Cu infiltrated material is only about 650-950℃. In the upgraded high-efficiency gas engine and high-explosion pressure diesel engine, the exhaust side seat ring is washed by high-temperature gas and repeatedly hit and slapped by the exhaust valve. Because of the installation of EGR exhaust gas recirculation device, the surface temperature of the seat ring can often reach 650-950℃. Under continuous high temperature and impact, the Cu particles infiltrated into the pores of the seat ring are prone to melting and loss, and the pores increase, so that the density, strength and wear resistance of the seat ring gradually decrease until failure; ② On the surface of the powder metallurgy copper-infiltrated seat ring, the hardness of the Cu alloy is much lower than the hardness of the hard phase of Co, Mo, and V alloys. Under high-temperature working environment, the seat ring with a high Cu content is easy to soften, and adhesive wear (material transfer) occurs between the seat ring and the valve cone surface, resulting in a decrease in the wear resistance of the seat ring until rapid failure; ③ The copper infiltration process is cumbersome and costly, and it is necessary to press and stack copper sheets. Missing stacking, multiple stacking, and poor weight control of copper sheets are all likely to cause fluctuations in the quality of the seat ring. Summary of the invention

[0004] Considering that the current copper-infiltrated valve seat rings are no longer competent for the task of friction pairs of valve trains of engines with ever-increasing high fuel efficiency and high explosion pressure under increasingly stringent emission standards, the present invention provides a high-density powder metallurgy valve seat ring and a preparation method thereof.

[0005] The technical solution of the present application is formed by mixing powder raw materials and then pressing and sintering; Among them, the mass content of elements in the powder raw material is: C: 1.0-2.0%, S: 0.3-1.2%, Mo: 6.0-14.0%, Co: 20.0-35.0%, W: 5.0-11.0%, V: 2.0-8.0%, Cr: 3.0-9.0%, Mn: 0.3-1.2%, Ni: 0.2-1.0%, P: 0.1-1.0%, Fe: balance.

[0006] Preferably, the mass content of elements in the powder raw material is: C: 1.2-2.0%, S: 0.5-0.8%, Mo: 9.0-12.0%, Co: 20.8-27.0%, W: 5.0-11.0%, V: 2.0-8.0%, Cr: 3.0-9.0%, Mn: 0.5-0.8%, Ni: 0.5-0.7%, P: 0.1-1.0%, Fe: balance.

[0007] Preferably, the powder raw material is formed by mixing a strengthening base powder, an alloy powder and basic additive components; the strengthening base powder contains W, Cr, V, P and Fe, wherein the P element exists in the form of FeP3.

[0008] Preferably, the alloy powder contains Mo, Co, Ni and Si elements.

[0009] Preferably, in the powder raw material, the mass fraction of the strengthened base powder is 55-65%, and the mass fraction of the high alloy powder is 32-42%.

[0010] The present application also provides a method for preparing a powder metallurgy valve seat ring, comprising the following steps: S1. Weigh the strengthening base powder, high alloy powder and other added components according to the mass ratio described in any one of the above items and mix them according to weight; S2, determining the shrinkage ratio of the powder after sintering, determining the size of the blank before sintering, and setting the pressing mold according to the size of the blank; S3, pressing the mixed powder into a molded blank with a density of 6.0-6.6 g / cm3 on a press; S4, sintering the seat ring blank in a push rod furnace at a high temperature of 1120-1200°C; S5, placing the sintered blank into a liquid nitrogen furnace at -170°C to -150°C for deep cooling treatment; S6. Place the seat ring blank after deep cryogenic treatment in a heat treatment furnace for heat treatment at 520-540°C for 2-4 hours, and then cool to room temperature.

[0011] When the valve seat ring of the present application enters the high temperature zone of the main sintering layer of the sintering furnace, the P in the matrix begins to diffuse into the alloy particles in the solid state, and the Fe-based strengthening base powder will dissolve part of the P atoms and transform into a two-phase structure of α-Fe + γ-Fe. When the sintering temperature rises and exceeds the P eutectic melting point of 1045-1065°C, according to the addition ratio of the liquid alloy powder, a 22-30% eutectic semi-liquid phase structure will be generated, so that the solid alloy particles are close to each other, and the particles are bonded to each other to form a metal bond with high bonding strength. It does not contain copper, and Cu will not melt and lose in high temperature and high explosion pressure environments. It can meet the harsh working environments of high temperature, high pressure, and no lubrication of high fuel efficiency gas engines and high explosion pressure engines. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 , 2 FIG. 1 is a microscopic diagram of the gas seat ring product material of the present invention, wherein Figure 1 This is a photo of the valve seat material porosity of the X100; Figure 2 This is a metallographic photograph of the valve seat material of the X500. DETAILED DESCRIPTION

[0013] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. In this specification, the size ratios in the drawings do not represent the actual size ratios, but are only used to reflect the relative position relationship and connection relationship between the components. Components with the same name or the same number represent similar or identical structures and are only for illustrative purposes.

[0014] First of all, it should be noted that in order to meet the working requirements of high-temperature and high-pressure gas engines and heavy-duty diesel engines, the industry usually first uses high-alloy ratio materials to press into seat ring blanks with a density of 6.3-6.7g / cm3, and then presses copper sheets according to 16-25% of the seat ring specific gravity, and then interlacedly stacks the seat ring and copper sheets together for high-temperature sintering. At the sintering temperature of 1100℃-1160℃, the copper sheets melt (the melting point of pure copper is 1083℃), and under the surface tension and capillary adsorption force, the Cu particles evenly penetrate into the pores between the alloy particles. After copper infiltration, the density of the seat ring can reach between 7.5-8.2 g / cm3, and the strength, thermal conductivity and wear resistance of the seat ring are correspondingly enhanced. However, in the upgraded high-efficiency gas engine and high-explosion pressure diesel engine, due to the installation of EGR exhaust gas recirculation device, the surface temperature of the exhaust side seat ring can often reach 650~950℃. Under continuous high temperature and impact, the Cu particles infiltrated into the pores of the seat ring are prone to soften, melt and flow away, and the pores increase, thereby gradually reducing the density, strength and wear resistance of the seat ring until failure; on the surface of the powder metallurgy copper-infiltrated seat ring, the hardness of the Cu alloy is much lower than the hardness of the hard phase of Co, Mo, and V alloys. Under high-temperature working environment, Cu is prone to bonding and wear between the Cu and the valve cone surface, resulting in abnormal wear and rapid failure of the seat ring; the copper infiltration process is cumbersome and costly, and it is necessary to press and stack copper sheets. It is easy to miss or over-stack when stacked manually or by machine, and poor weight control of the copper sheets can easily cause fluctuations in the quality of the seat ring.

[0015] The present application provides a copper-free powder metallurgy valve guide ratio and preparation method, so it does not need to be treated by copper infiltration process. The present application is mainly to solve a series of problems existing under high temperature conditions such as softening of the seat ring under high temperature state caused by the addition of copper elements, and to provide a non-copper infiltrated high-density and high-wear-resistant powder metallurgy valve seat ring. The technical solution of the present invention uses a strengthening base powder containing elements such as Fe and P, which accounts for about 55%-65% of the total weight, and adds a certain proportion of high alloy powder (containing Co, Mo, Ni, Si). The Fe and P elements in the strengthening base powder are generally smelted together in the form of Fe3P. The present application also adds other additive components such as a certain solid lubricant, and generates 22-30% of a semi-liquid phase during high-temperature sintering, which penetrates into the pores of the alloy, so that the solid phase particles of alloys such as Co, Mo, W, Cr are in a semi-suspended state, and the solid phase particles are displaced and adjusted to each other under the action of the surface tension of the liquid phase, until finally a tight combination is achieved. In this process, the volume of the sintered seat ring shrinks rapidly and the density increases rapidly.

[0016] In this embodiment, the preparation method of the high-density engine valve seat alloy material is: S1. According to the given ratio requirements, the strengthening base powder, high alloy powder and other added components are weighed and mixed according to weight parts; S2. Determine the shrinkage ratio of the powder after sintering, determine the size of the blank before sintering according to the required actual size and shrinkage ratio, and set the pressing mold according to the size of the blank. Usually, considering the impact of shrinkage, the outer diameter of the blank is designed to be 2-3mm larger than the finished seat ring; during molding, the height of the seat ring blank should be 0.5-1mm higher than the finished product to ensure the shrinkage margin of the seat ring.

[0017] S3. Press the mixed powder into a molded blank with a density of 6.0-6.6 g / cm3 on a press.

[0018] S4. The seat ring blank is sintered at high temperature in a push rod furnace at a sintering temperature of 1120-1200°C.

[0019] S5. Place the sintered blank into a liquid nitrogen furnace at -170°C to -150°C for deep cooling treatment.

[0020] S6. Place the seat ring blank after deep cryogenic treatment in a heat treatment furnace for heat treatment at 520-540°C for 2-4 hours, and then cool to room temperature.

[0021] S7. After the cold and hot treatment, the seat ring blank is subjected to B grinding (grinding the upper and lower end faces), intermediate grinding (preliminary grinding of the outer circle), NC processing (sealing surface and seat surface turning), and fine grinding (external circle fine grinding). The finished product is inspected, oiled, and packaged.

[0022] Example 1 In order to facilitate the control of the raw material configuration process, the powder metallurgy powder mixing process is formed by mixing a variety of prefabricated mixed powders. It is also to ensure good contact and bonding between specific elements before pressing. Therefore, in this embodiment, 55% by mass of strengthening base powder and 42% by mass of high alloy powder are provided for mixing. During mixing, 1.2% by mass of carbon element, 0.8% by mass of sulfur element and 0.8% by mass of manganese element are also added. After the above powders are mixed evenly, they are pressed and formed by the above method, and the valve seat ring is obtained by heat treatment after sintering.

[0023] The reinforced base powder contains 0.1% phosphorus by mass, in which the phosphorus is added to the reinforced base powder in the form of Fe3P compound. In addition, it also includes 5% tungsten, 3% chromium, 2% vanadium, and the balance is iron. The alloy powder component contains 12.0% molybdenum, 27% cobalt, and 0.7% nickel by mass.

[0024] Example 2 The preparation method is the same as that in Example 1, providing 55% by mass of a strengthening base powder and 42% by mass of a high alloy powder for mixing, and during the mixing, 1.2% by mass of a carbon element, 0.8% by mass of a sulfur element, and 0.8% by mass of a manganese element are also added. After the above powders are mixed evenly, they are pressed and formed by the aforementioned method, and then sintered and heat-treated to obtain a finished valve seat ring.

[0025] The reinforced base powder contains 0.3% phosphorus by mass, in which the phosphorus is added to the reinforced base powder in the form of Fe3P compound. In addition, it also includes 5% tungsten, 3% chromium, 2% vanadium, and the balance is iron. The alloy powder component contains 12.0% molybdenum, 27% cobalt, and 0.7% nickel by mass.

[0026] For other examples, refer to the table below.

[0027]

[0028] The valve seat ring obtained in the above embodiment was subjected to performance testing and high-temperature friction and wear testing. The high-temperature wear testing was performed using a high-temperature wear testing machine according to industry standards. The experimental conditions and results are shown in the following table.

[0029] The seat ring blank is composed of reinforced liquid alloy powder (including Fe3P), high alloy powder and solid lubricant. During the high-temperature sintering stage, as the temperature of the sintering furnace increases, the P in the liquid alloy powder begins to diffuse into the alloy particles in the solid state, and the Fe-based alloy powder will dissolve some P atoms and transform into a two-phase structure of α-Fe + γ-Fe. When the sintering temperature rises and exceeds the P eutectic melting point of 1045-1065℃, according to the addition ratio of the liquid alloy powder, a 22-30% eutectic semi-liquid structure will be generated (generally based on filling the pores between the hard phases). Furthermore, the high melting point alloy particles such as W, Co, and Mo added to the material will be surrounded by the liquid phase and in a suspended state. The liquid phase components wet the alloy particles at an angle of 0-40° (the smaller the wetting angle, the better the wetting effect), and they will shift under the surface tension of the liquid phase and the capillary adsorption force. The solid phase alloy particles will move closer to each other, and the particles will bond to each other to form a metal bond with high bonding strength; the liquid phase will penetrate into the gaps between the alloy particles, thereby achieving a tight arrangement. As the insulation time increases, the pores in the seat ring change from being interconnected to being isolated, and the pore shape changes from a long strip to an ellipse with a diameter of ≤10µm and even a sphere, and the number of pores is greatly reduced. The seat ring shrinks in volume, densification is formed, and the seat ring density reaches 7.6-8.3g / cm3.

[0030] By adding liquid phase strengthening alloy powder for semi-liquid phase sintering, the number of pores in the seat ring is greatly reduced, and the pores are transformed from long connected pores into isolated, elliptical or spherical tiny holes with a diameter of ≤10µm. The seat ring is not infiltrated with copper and reaches a high density of 7.6-8.3g / cm3; at the same time, the crushing strength of the seat ring is increased to 800-1000MPa, which is an average increase of about 52% over the crushing strength of ordinary high-alloy copper-infiltrated seat rings (500-650MPa), reducing the risks of fracture, collapse and internal invisible cracks common in high-alloy seat rings.

[0031]

[0032] The present invention contains W (5-11.0%) and Cr (3.0-9.0%) in the strengthening base powder; W forms high-hardness and high-melting-point eutectic carbides WC and W2C with C through solid solution strengthening and dispersion strengthening, which significantly improves the high-temperature stability and wear resistance of the seat ring; ② The added alloy powder contains precious metals Co: 20-35% and Mo: 6-14%. Co can refine the grains and has good thermal strength. It forms (CoWCr)4C carbide with C, W, Cr, etc., improves the high-temperature hardness and strength of the seat ring, improves the thermal fatigue resistance and oxidation resistance, and makes the seat ring matrix not easy to overheat; the hardness of the liquid phase sintered seat ring after cold and hot treatment reaches HRC 52-62; ③ In the semi-liquid state, the added Co and Mo alloy particles undergo displacement and chemical reaction, and form a Fe-Co-Mo-C alloy strengthening phase with metal bonds with C and the matrix, which further improves the wear resistance and strength of the seat ring at high temperature, and greatly reduces the plastic deformation and fatigue wear of the material at high temperature; ④ Add 3-9% Cr to improve oxidation resistance and corrosion resistance; ⑤ Add an appropriate amount of Ni powder to further reduce the porosity and spheroidize, and promote densification sintering.

[0033] 1.5-2.5% solid lubricant MoS2 is added in this application. This lubricant has a very low friction coefficient, generally 0.03-0.1. A protective film is formed on the surface of the seat ring to reduce the direct contact between the valve cone surface and the seat ring sealing surface, thereby reducing the occurrence of adhesive wear between the seat ring and the valve.

[0034] In order to achieve the ideal semi-liquid phase sintering effect and ensure that the high temperature hardness, density, strength, wear resistance, etc. of the seat ring meet the material design requirements, the proportion of various elements must be strictly controlled. In order to generate a eutectic liquid phase, the reinforced liquid phase alloy powder of the present invention contains a certain proportion of phosphorus iron powder (Fe3P). Within a certain range, as the P content increases, the sintering and heat preservation time is extended, the eutectic liquid phase increases, the pore distribution changes from interconnected to isolated, the number decreases, and the pore shape changes from irregular to elliptical and spherical. When the P content is too much, the strength and wear resistance of the seat ring decrease rapidly, and the brittleness of the matrix increases. In the present invention, the C element not only forms an iron-carbon alloy with the matrix, but also combines with W, Co, Mo, etc. to form alloy carbides. If the C content is too low, the number of carbides decreases, and the hardness, strength, and wear resistance of the seat ring decrease; if the C content is too high, the direct contact between the alloy powder particles is hindered, the sintering process is hindered, and it is not conducive to densification and pore spheroidization. At the same time, when the C content is very high, a small amount of free graphite is unavoidably present in the race, which has a notch effect on the mechanical properties of the race, causing the strength and wear resistance of the race to drop rapidly.

[0035] The above content only describes the preferred implementation mode of the present invention, and does not limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solution of the present invention by ordinary technicians in this field should fall within the protection scope determined by the claims of the present invention.

Claims

1. A powder metallurgy valve seat ring, characterized in that: It is made by mixing powder raw materials and then pressing and sintering; Among them, the mass content of elements in the powder raw material is: C: 1.0-2.0%, S: 0.3-1.2%, Mo: 6.0-14.0%, Co: 20.0-35.0%, W: 5.0-11.0%, V: 2.0-8.0%, Cr: 3.0-9.0%, Mn: 0.3-1.2%, Ni: 0.2-1.0%, P: 0.1-1.0%, Fe: balance.

2. The powder metallurgy valve seat insert according to claim 1, characterized in that: in, The mass contents of the elements in the powder raw material are: C: 1.2-2.0%, S: 0.5-0.8%, Mo: 9.0-12.0%, Co: 20.8-27.0%, W: 5.0-11.0%, V: 2.0-8.0%, Cr: 3.0-9.0%, Mn: 0.5-0.8%, Ni: 0.5-0.7%, P: 0.1-1.0%, Fe: balance.

3. The powder metallurgy valve seat insert according to any one of claims 1 to 2, characterized in that: The powder raw material is formed by mixing a strengthening base powder, an alloy powder and basic additive components; the strengthening base powder contains W, Cr, V, P and Fe, wherein the P element exists in the form of FeP3.

4. The powder metallurgy valve seat insert according to claim 3, characterized in that: The alloy powder contains Mo, Co, Ni and Si elements.

5. The powder metallurgy valve seat insert according to claim 3, characterized in that: In the powder raw material, the mass fraction of the strengthening base powder is 55-65%, and the mass fraction of the high alloy powder is 32-42%.

6. A method for preparing a powder metallurgy valve seat ring, characterized in that: The steps include: S1. According to the mass ratio described in any one of claims 1 to 5, the strengthening base powder, the high alloy powder and other added components are weighed and mixed by weight; S2, determining the shrinkage ratio of the powder after sintering, determining the size of the blank before sintering, and setting the pressing mold according to the size of the blank; S3, pressing the mixed powder into a molded blank with a density of 6.0-6.6 g / cm3 on a press; S4, sintering the seat ring blank in a push rod furnace at a high temperature of 1120-1200°C; S5, placing the sintered blank into a liquid nitrogen furnace at -170°C to -150°C for deep cooling treatment; S6. Place the seat ring blank after deep cryogenic treatment in a heat treatment furnace for heat treatment at 520-540°C for 2-4 hours, and then cool to room temperature.

Citation Information

Cited By

  • Powder metallurgy material and preparation method thereof, friction pair part and suspension gear pump

    CN121518963A